(untitled) (Biological Sciences - PJSIR, 2021)
Citrus is one of the most commonly used as a fruit in Pakistan. To estimate their elemental profile citrus were collected from five different tehsils of Sargodha district. Elemental analysis was carried out by atomic absorption spectrophotometer. There results showed that citrus fruits have riched source of minerals and have highest concentrations of Cu (2.71 mg/Kg), Mn (0.1633 mg/Kg) and Zn (31.72 mg/Kg) noted in T1 (Silanwali), while the maximum concentrations of Mg (65.247 mg/Kg), Cr (0.343 mg/Kg), P (1.146 mg/Kg), Co (0.536 mg/Kg), K (133.01 mg/Kg) were found in T2 (Sahiwal), T4 (Kotmomin) and T5 (Bhehra), respectively. Fluctuation in elemental profile of Citrus reticulata may be attributed to spatial variations or may be due to agro-climatic conditions that varies in all tehsils.